Coronavac covid-19 vaccine-induced anaphylaxis: Clinical characteristics and revaccination outcomes - Wannada Laisuan (2022)
Anaphylaxis to CoronaVac, an inactivated vaccine against COVID-19, is extremely rare. We report 12 cases of anaphylaxis after CoronaVac administration, focusing on clinical characteristics and management outcomes. Skin test and graded vaccine challenge were successfully performed in our cases and might be considered if an inactivated vaccine is the only remaining option.